ORIGIN OF MAGNETITE IN OXIDIZED CV CHONDRITES: IN SITU MEASUREMENT OF OXYGEN ISOTOPE COMPOSITIONS OF ALLENDE MAGNETITE AND OLIVINE - Choi B.G.; McKeegan K.D.; Leshin L.A.; Wasson J.T. (My University, 1997)
Magnetite in the oxidized CV chondrite Allende mainly occurs as spherical nodules in porphyritic-olivine (PO) chondrules, where it is associated with Ni-rich metal and/or sulfides. To help constrain the origin of the magnetite, we measured oxygen isotopic compositions of magnetite and coexisting olivine grains in PO chondrules of Allende by an in situ ion microprobe technique. Five magnetite nodules form a relatively tight cluster in oxygen isotopic composition with δ18O values ranging from -4.8 to -7.1%% and δ17O values from -2.9 to -6.3%%. Seven coexisting olivine grains have oxygen isotopic compositions from -0.9 to -6.3%% in δ18O and from -4.6 to -7.9%% in δ17O.The Δ17O values of the magnetite and coexisting olivine do not overlap; they range from -0.4 to -2.6%%, and from -4.0 to -5.7%%, respectively. Thus, the magnetite is not in isotopic equilibrium with the olivine in PO chondrules, implying that it formed after the chondrule formation. The Δ17O of the magnetite is somewhat more negative than estimates for the ambient solar nebula gas. We infer that the magnetite formed on the parent asteroid by oxidation of metal by H2O which had previously experienced minor O isotope exchange with fine-grained silicates.
Keywords: MAGNETITE; OLIVINE; O-18O-16; O-17O-16; ION PROBE DATA; CHONDRITES; METEORITES